Kajian Penentuan Arah Kiblat Dengan Sensor Magnetik Kompas Android - Yusuf Nurqolbi DY; Ulil Albab Al aulia Alpaten; Kurniawan Kurniawan (Astroislamica: Journal of Islamic Astronomy, 2024)
The reliability of compass sensors in accurately determining the Qibla direction remains a matter of skepticism. This uncertainty arises mainly from the fact that compass sensors are highly susceptible to interference from the surrounding magnetic field. As a result, the north indicated by these sensors does not correspond to true geographical north; rather it reflects the orientation of the earth's magnetic field. To explore this issue further, a field research methodology was employed, utilizing qualitative data analysis to assess the findings. Based on the measurement results, there was an average difference of 2° 38' 23.53”. Internally, the function of the compass sensor is closely related to the capabilities of the GPS system and the effectiveness of the supporting sensors that work with it. These internal components must function accurately and cohesively to provide precise direction readings. On the other hand, external factors also play an important role in the performance of the compass sensor. According to the majority of scholars, this obligation involves orienting oneself within a certain range of the actual Qibla location. This range is usually defined as being within 45° degrees to the right or left of the actual direction of the Kaaba. If one's orientation exceeds this 45° degree deviation, it is generally considered that one is no longer facing the Qibla correctly.